Recognition of a Monument Called Sharbatkhāneh in Afushteh, based on the Deed of ‎Endowment of Seyyed-i Waqif’s Properties - naqmeh asadi chime; Niloufar Malek; Hamidreza Jayhani (صفه)
Stories narrated by ordinary people for some architectural works can be considered as a source for ‎recognizing them. Still, in some cases, these beliefs and myths are so accepted by researchers ‎without any doubt or challenge. An example of this belief is the story narrated by the people of ‎Afushteh, according to which a decorated pavilion shaped monument is called Sharbatkhāneh. The ‎name Sharbatkhāneh, which seems to be derived from a narration about Taj al-Din Hassan-i ‎Hosseini or Seyyed-i Waqif, is so well established that being invalid never comes to mind. ‎However, a review of the only available document from the buildings of Seyyed Hassan-i Waqif in ‎Afushteh, that is, the deed of endowment of this building, shows that this name is not very ‎documented; In other words, there is no such name in the deed of the endowment. In the same ‎document, another building called Chāhārṣoffeh and Ṭanabī is introduced. In recent years, a study ‎of documents and structures in Afushteh by Hossein Azam-i Wāqifī has suggested that the ‎Chāhārṣoffeh and Sharbatkhāneh buildings were the same without a thorough examination of the ‎reasons. The primary purpose of this study is to clarify how accurate and provable such a ‎hypothesis is. However, proving this assumption does not determine whether the building is ‎Sharbatkhāneh or not, because Chāhārṣoffeh refers to it architecturally and Sharbatkhāneh ‎mentions its function. So the next goal is to find the function of the building, first by validating the ‎name Sharbatkhāneh for this structure and then by examining the names that have been applied to ‎it in other sources. The current research tries to study the historical documents as well as the ‎physical aspects of the building by the aid of the historical interpretive method. The result of this ‎study first confirms the conformity of the Chāhārṣoffeh and Sharbatkhāneh, and secondly chooses ‎the name Timurid Chāhārṣoffeh instead of the use of names derived from unknown and invalid ‎functions.‎